2012
DOI: 10.1177/0020764012437322
|View full text |Cite
|
Sign up to set email alerts
|

Perceived human rights violation in persons with mental illness: Role of education

Abstract: Empowering people with mental illness by providing adequate opportunity to pursue education will play an important role in fulfilling the obligation of the United Nations Convention on the Rights of Persons with Disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Low level of education, low income, unhealthy lifestyle and occupational conditions and stress are among the socioeconomic factors often associated with poor health [ 23 ]. Evidence shows that illiteracy and low level of education marginalize people [ 24 ], decrease the access and utilization of available mental health services and interfere with some valuable goals in a community such as health promotion and access to social support and health care services [ 25 , 26 ]. Low level of education is also correlated with poverty, unemployment and incarceration [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low level of education, low income, unhealthy lifestyle and occupational conditions and stress are among the socioeconomic factors often associated with poor health [ 23 ]. Evidence shows that illiteracy and low level of education marginalize people [ 24 ], decrease the access and utilization of available mental health services and interfere with some valuable goals in a community such as health promotion and access to social support and health care services [ 25 , 26 ]. Low level of education is also correlated with poverty, unemployment and incarceration [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For people suffering from mental disorders, there have been violations of basic human rights and freedoms, as well as denials of civil, political, economic, and social rights, in both institutions and communities. In a recent descriptive study carried out among recovered mentally ill demonstrated that irrespective of gender,[ 35 ] literacy,[ 36 ] socioeconomic status[ 37 ] and residence,[ 38 ] human rights violations are occurring at family and community level. The current study also reveals negative attitudes of participants regarding social participation of mentally ill in the community as they cited they would be ashamed if people knew that someone in their family had been diagnosed with a mental illness as well they would not want people to know about their illness.…”
Section: Discussionmentioning
confidence: 99%
“…Family members play a vital role in India toward any decision-making,[2326] and hence, the donor is not the sole decision-making authority for the deceased organ donation; among the nursing participants in our study, 65.3% of them agreed that permission from the nearer family member is also very essential. Other similar studies have shown that 60%–80% of the study participants agreed to the same.…”
Section: Discussionmentioning
confidence: 97%